Physicochemical compatibility of high concentration drugs usually Y-site administered in intensive care units. Issue 2 (3rd November 2014) - López-Cabezas, Carmen; Guerrero, Laura; Molas, Gloria; Anglada, Helena; Soy, Dolors
Abstract : Objective: To study the physical compatibility of 63 binary mixtures of drugs usually Y-administered in intensive care units, and to evaluate the chemical stability of the most relevant binary mixtures. Methods: Binary mixtures were aseptically prepared in a 1:1 ratio. End-points were measured in triplicate immediately after and 4 and 24 h after preparation. Chromatographic techniques were all validated under the study conditions, following international guidelines. All methods were proven to be stability-indicating. Main outcome measures: Incompatibility was defined as the presence of haziness, colour change or precipitation compared with the parent drug solution. Chemical instability was considered present when >5% variation in the concentration of any of the components in the mixture was observed and/or pH values were outside the stability range for any of the drugs in the mixture. Results: This study demonstrated the physicochemical Y-site compatibility of: (i) dopamine or dobutamine at 8 mg/mL with methadone 0.2 mg/mL in both 5% dextrose (5%D) and normal saline (NS); (ii) dopamine or dobutamine with midazolam 4 mg/mL in 5%D but not in NS; (iii) methadone with midazolam in 5%D and NS, and methadone with esomeprazole or pantoprazole 0.32 mg/mL in NS. Results demonstrated the incompatibility of: (i) dobutamine with furosemide in NS; and (ii) midazolam 4 mg/mL with esomeprazole in NS. Conclusions: This study provides information about the physicochemical compatibility of ordinary mixtures, at high concentrations, commonly used in intensive care units. These results might help to improve drug safety management in the critically ill patient.